Randomised controlled study for comparing the efficacy of tretinoin 0.05% cream alone versus tretinoin combined with microdermabrasion in adult patients of alopecia areata - Kaur, Navneet; ., Ankita; Maheshwari, Kriti; Menghani, Gaurav; Vyas, Kapil; Gupta, Kalpana; Singh, M. K. (International Journal of Research in Dermatology, 2022)
Background: Alopecia areata is non-scarring autoimmune disease. It is characterized by discrete patches of non-scarring hair loss and may involve scalp, eyebrows, eyelashes, beard, axillary hair and pubic hair. Therapeutic armamentarium is expanding with detailed elucidation of patho-mechanisms and emergence of new drugs like janus kinase inhibitors. Methods: An interventional prospective study was conducted on the patients which were randomized into two groups (19 patients each) by lottery system, patients of group A were treated with tretinoin 0.05% cream whereas in group B patients microdermabrasion (MDA) was performed at baseline, 3rd, 6th, 9th and 12th weeks in addition to the application of tretinoin 0.05% cream daily. Results: The mean GPI% in Group A was 6.26±5.13 and group B was 32.63±15.29% which is significantly higher at the end of 2 weeks (p=0.001). At 8 weeks, mean GPI in group A was 10.95±6.79 and in group B was 51.42±12.42 which was also significantly higher (p=0.026) as compared to group A. Similarly mean VAS in group A at 2 weeks and 8 weeks (0.62±0.51 and 1.1±0.67) and in group B was (3.27±1.53 and 5.16±1.26) which was significantly higher with difference in p value at 2 weeks between the two groups was p=0.001 and at 8 weeks was p=0.017. There was significant change in GPI and VAS at 8 weeks, in group A as compared to group B. Conclusions: This study revealed that tretinoin was more effective than the combination with MDA.